A disaggregate travel demand model. - Richards, Martin Gomm (Saxon House Studies, 1975)
Modified version of a report entitled Disaggregate and simultaneous travel demand models: a Dutch case study prepared by Buro Goudappel en Coffeng BV, in association with Campridge Systematics Inc.